Influence of Devolved Enterprise Funds on Household Welfare in Kenya - Shibairo, Peter; Ngaruko, Deus; Wawire, Nelson (International Journal of Economics, 2023)
Purpose: Devolved enterprise funds would contribute to increased entrepreneurship and household welfare in Kenya, leading to reduced poverty levels and improved living standards. The extent of the impact of devolved enterprise funds on household welfare in Kenya is uncertain. Despite the funds being available, many entrepreneurs in Kenya still struggle to access capital and other resources needed to start and grow their businesses. This has limited the potential benefits of devolved enterprise funds on household welfare. This study investigated the influence of devolved enterprise funds on household welfare in Kenya. Methodology: The study employed a non-experimental pooled cross-sectional research design. The study targeted the households listed in the 2015/2016 Kenya Integrated Household Budget Survey which indicated the residence of households' owners from which a random sample of 384 households was generated using the Fisher's formula. Cross sectional data were collected from selected households using structured questionnaire. Random utility maximization theory was used to determine people's choice, preferences and decision making. Simple linear regression model was used to estimate the relationship between variables. The data was presented in tables. Findings: Findings revealed that devolved enterprise funds had a significant positive influence on household welfare in Kenya. Therefore, household welfare will improve if devolved enterprise funds positively influence the welfare of many households in Kenya. Unique Contribution to Theory, Practice and Policy: The study recommends that efforts should be made to simplify and streamline the application and disbursement processes for enterprise funds, particularly for women and youth entrepreneurs who may face additional barriers to accessing funds.